Evaluation of a project to engage patients in the development of a patient‐reported measure for HIV care (the I‐Score Study). (29th October 2018) - Lessard, David; Engler, Kim; Toupin, Isabelle; Routy, Jean‐Pierre; Lebouché, Bertrand
Abstract: Background: Patient engagement (PE), patients' meaningful involvement in research through partnerships and sensitivity to their expertise, is receiving attention. However, PE initiatives are poorly reported and little is known about patients' perspective on PE. Objective: To document and evaluate the first phase (22 months) of a PE Project for the I‐Score Study which is developing a patient‐reported measure of HIV treatment adherence barriers, we describe the nature of PE conducted, determine the level of PE achieved and present its impacts from the engaged patients' perspective. Setting and participants: A Montreal‐based committee of ten people with HIV was recruited from community and clinical settings and participated in: I‐Score study decision making, knowledge dissemination, research on the experience of people with HIV and the PE project's evaluation. Methods: The evaluation followed a convergent parallel mixed‐methods design. Data collection included participant observation, a satisfaction survey and meeting minutes/transcriptions. Analysis entailed reporting PE activities, generating descriptive statistics and thematically analysing qualitative material. Results: PE consisted of twelve meetings, including two focus groups (needs assessment), in addition to four knowledge dissemination activities. PE levels showed an increase: the first four regular meetings entailed information/consultation, while subsequent meetings reached implication/collaboration. Regarding impacts, patients indicated high and stable satisfaction rates ( M = 4.4/5; SD = 0.76). Furthermore, thematic analysis identified "positive interactions, " "co‐learning, " "self‐determination, " and "the collective management of confidentiality" as important PE impacts for engaged patients. Conclusion: This PE Project evaluation highlighted growing engagement levels, high satisfaction rates and the importance of a patient‐centric approach to PE.